Re: Bag et al.: One week of nitrofurantoin before percutaneous nephrolithotomy significantly reduces upper tract infection and urosepsis: a prospective Controlled Study (Urology 2010;77:45-49) - Feng, Yih Chai; Kamarulzaman, Mohd Nazli; Jiffre, Din; Hamid, Ghazali (Elsevier, 2011)
OBJECTIVES: